The Impact of Physician Assistants on a Breast Reconstruction Practice: Outcomes and Cost Analysis. Issue 3 (September 2017) - Chao, Albert H.; Yaney, Alexander; Skoracki, Roman J.; Kearns, Patrick N.
Abstract : Background: Physician assistants (PAs) are commonly employed in plastic surgery. However, limited data exist on their impact, which may guide decisions regarding how best to integrate them into practice. Methods: A review of the practices of 2 breast reconstructive surgeons was performed. A comparison was made between a 1-year period before to a 1-year period after the addition of a PA into practice. The practice model was a one-to-one pairing of a plastic surgeon and a PA. Results: A total of 4141 clinic encounters and 1356 surgical cases were reviewed. After the addition of PAs, there was a significant increase in relative value units (1057 vs 1323 per month per surgeon, P < 0.001). Operative times were similar with and without PAs ( P = 0.45). However, clinic encounter times for surgeons were shorter for all visit types when patients were first seen by a PA before the surgeon: global follow-up ( P = 0.03), other follow-up ( P = 0.002), consultation ( P = 0.76), and preoperative ( P = 0.02), translating to 9 additional patients seen per day. Charges ( P = 0.001) and payments ( P = 0.007) also increased, which offset the cost of using a PA. However, the financial contribution from PA involvement as first assistant in surgery was limited (5.2%). The peak effect of PAs was observed between the third and fourth quarters. Conclusions: In breast reconstruction, PAs primarily enhance the efficiency of plastic surgeons, particularly in the clinic, with downstream clinical and financial gains of an indirect nature for surgeons.